PENGARUH KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN PADA PRODUK SHAMPO SUNSILK - Astrid Lolis Sintiani Manao (Universitas Nias Raya, 2026)
This study used qualitative research methods. This type of research data uses primary data and secondary data. Primary data can be obtained from distributing questionnaires to respondents, while secondary data is data obtained from other existing sources, such as journals, books and others. This research was conducted on students from the Faculty of Economics and Business, Nias Raya University with a total of 86 respondents. The data analysis method used is simple linear regression analysis. The purpose of this research is to determine the effect of product quality on consumer loyalty to Sunsilk shampoo products (case study of students from the Faculty of Economics and Business, Nias Raya University). From the results of data analysis carried out through partial statement items, it is stated that the Product Quality variable has a positive and significant effect on Consumer Loyalty